SOCIAL ADAPTATION SKILLS OF PRESCHOOL CHILDREN AND IMPROVING THEIR QUALITY - Maryambibi Djumaniyazovna Abdullayeva (Web of Journals Publishing, 2024)
To fix adaptation, it is necessary to have both of these criteria, since both a feasible level of productivity and position in the team must be supported by satisfaction with them, and satisfaction itself without recognition in the team or any reference group and without a focus on productive activity is insufficient for the adaptation of a socialized personality and is more often a compensatory reaction to maladjustment or a sign of opportunism. The level of satisfaction as a criterion and indicator of personal adaptation is very sensitive and requires clarification.
Keywords: adaptation, criterion, personality, preschool education, children, pedagogy.